APLIKASI ZAT TUMBUH UNTUK MENYEREMPAKKAN KEMASAKAN BUAH JARAK PAGAR (Jatropha curcas L.) - Kartika Kartika; Endah Retno Palupi; Memen Surachman (JURNAL AGROTROPIKA, 2012)
One of the major constraints in Jatropha oil production is asynchronous fruit ripening, hence harvesting needs to be carried out accordingly which lead to drudgery. Therefore, an experimental study on the use of plant growth regulators was designed to induce synchronous fruits ripening. The study was conducted at the Jatropha Indocement Tbk PT Citeurep from January-June 2010. Test seed vi-ability and vigor was conducted in greenhouse Leuwikopo Experimental Garden, Bogor Dramaga. While the oil content test was conducted in the Department of Industrial Technology Testing Laboratory of Agricultural IPB. This research was conducted in two phases. In the first stage used factorial randomized block design. The first factor is the dose etephon 200,400,600,800, 1000 and 1200 ppm while the second factor is the time of application etephon ie 40 and 45 days after anthesis. The second phase also uses a factorial randomized block design. The first factor is the dose etephon 0,100,200, 300 and 400 ppm, while the second factor is the time of application ie 40 and 45 days after anthesis. Application of etephon at 200 ppm on 40 day after anthe-sis shorten the fruit maturation hence more synchronous fruit ripening in rainy season, but not in dry season when fruits ripened synchronously. The quality of the seed and kernel were not affected by etephon application.  Keywords: Jatropha curcas, growth regulator, etephon, simultaneity of fruit maturity